(untitled) (Psychology Travelogs, 2024)
This article examines the phenomenon of frustration and frustration tolerance, focusing on their manifestations within the families of military servants’. It provides precise definitions of the concepts "frustration" and "frustration tolerance," emphasizing their relevance in the specific living conditions of military servants families’ members. The causes of frustration in this population group have both external and internal origins, which complicates the process of adaptation to the specific living conditions related to military service. The core components of frustration-emotional, physiological, and cognitive-are analyzed, along with the external and internal factors contributing to the emergence of frustration in this group of population. Particular attention is given to identifying emotional, cognitive, and behavioral manifestations of frustration tolerance as crucial aspects of psychological resilience. The study explores the role of frustration tolerance as a vital psychological resource that promotes emotional stability, adaptation to stressful situations, and the preservation of mental health in the conditions of war in Ukraine. Various approaches to fostering frustration tolerance are discussed, including emotional self-regulation, cognitive flexibility, and stress management techniques. These methods are positioned as effective tools for enhancing the well-being for the members of military servants’ families under stressful conditions. The article concludes by underscoring the importance of continued research into frustration tolerance, particularly regarding its application in psychological support programs for military families. Such programs aim to strengthen their ability to adapt to life’s challenges and maintain emotional and mental stability in demanding circumstances.